Determinants of Vitamin D Levels in Italian Children and Adolescents: A Longitudinal Evaluation of Cholecalciferol Supplementation versus the Improvement of Factors Influencing 25(OH)D Status - Stefano Stagi; Paola Pelosi; Massimo Strano; Giovanni Poggi; Cristina Manoni; Maurizio de Martino; Salvatore Seminara (International Journal of Endocrinology)
Objective. This paper aims to assess 25(OH)D levels in Italian children and adolescents identifying risk factors for 25(OH)D deficiency and to evaluate whether a normal 25(OH)D value can be restored in 25(OH)D-deficient patients. Methods. We evaluated 25(OH)D levels in 679 Italian children and adolescents (≤10, 11–20, 21–30, and >30 ng/mL were defined as severe deficiency, deficiency, insufficiency, and sufficiency, resp.). Of these, 365 25(OH)D-deficient were followed up for 1 year; 205 were treated with cholecalciferol (Arm A: 400 I.U.) and 160 by improving the environmental variables influencing 25(OH)D levels (Arm B). Results. At cross-sectional evaluation, 11.3% showed sufficiency, 30.0% insufficiency, and 58.7% 25(OH)D deficiency. Mean 25(OH)D was 19.08±8.44 ng/mL. At the enrollment time (T0), no difference was found between Arms A and B with respect to distribution and 25(OH)D levels. At end time (T1) 26.0% (29.7% in Arm A versus 20.6% in Arm B) showed sufficiency, 38.4% (42.0% versus 34.4%) insufficiency, and 35.6% (28.3% versus 45.0%) 25(OH)D deficiency. Mean 25(OH)D level was 23.71±6.83 ng/mL. Conclusions. Neither changes of lifestyle nor 400 I.U. cholecalciferol supplementation alone appears to be sufficient to restore adequate 25(OH)D levels.